Ethnography in Community Psychology: Promises and Tensions. Issue 1 (15th April 2014) - Case, Andrew D.; Todd, Nathan R.; Kral, Michael J.
Abstract: Community psychology recognizes the need for research methods that illuminate context, culture, diversity, and process. One such method, ethnography, has crossed into multiple disciplines from anthropology, and indeed, community psychologists are becoming community ethnographers. Ethnographic work stands at the intersection of bridging universal questions with the particularities of people and groups bounded in time, geographic location, and social location. Ethnography is thus historical and deeply contextual, enabling a rich, in‐depth understanding of communities that is aligned with the values and goals of community psychology. The purpose of this paper is to elucidate the potential of ethnography for community psychology and to encourage its use within the field as a method to capture culture and context, to document process, and to reveal how social change and action occur within and through communities. We discuss the method of ethnography, draw connections to community psychology values and goals, and identify tensions from our experiences doing ethnography. Overall, we assert that ethnography is a method that resonates with community psychology and present this paper as a resource for those interested in using this method in their research or community activism.